Language Variation in the Linguistic Landscape of Mosques in West Surabaya - Ziya'uddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines language variation in the linguistic landscape of mosques in West Surabaya. Linguistic landscape is understood as the visual representation of language in public spaces that reflects both communicative and symbolic functions within a community. The study focuses on the types of languages used, patterns of language combination, and their distribution across various mosque areas, such as façades, main prayer halls, information boards, and activity banners. The research employs a descriptive qualitative approach supported by simple quantitative analysis to identify language distribution patterns. Data were collected through visual documentation and classified based on language type and context of use. The analysis was conducted to identify language variations and their functions as both sacred and informative media.The results show that monolingual linguistic landscapes are more dominant than bilingual ones. Indonesian is predominantly used as a medium of information and direction for worshippers, while Arabic is mainly used in religious elements such as prayers, Qur’anic verses, and calligraphy. In addition, bilingual forms of Indonesian–Arabic and Arabic–Indonesian were also found, functioning to strengthen understanding as well as Islamic identity within the mosque environment. These findings indicate that the linguistic landscape of mosques functions not only as a medium of information but also as a representation of the religious and social identity of the community.